2011
DOI: 10.1038/pr.2011.21
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance imaging of the neonatal piglet brain

Abstract: ArticlesTranslational Investigation nature publishing group INTRODUCTION: appeal for the domestic pig as a preclinical model for neurodevelopmental research is increasing. One limitation, however, is lack of magnetic resonance imaging (MRI) methods for brain volume quantification in the neonatal piglet. The purpose of this study was to develop and validate MRI methods for estimating brain volume in piglets. RESULTS:The results showed that MRI and manual segmentation reliably estimated the changes in volume of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 38 publications
0
28
0
Order By: Relevance
“…Despite the prevalence of this problem, the mechanisms for the effects of iron deficiency on cognition are poorly understood. The pig may be an excellent preclinical model in which to study the mechanisms underlying iron deficiency-induced cognitive impairment in human neonates due to similar brain growth and structure (27,28,30), limited iron stores at birth (33), and the ease of early life cognitive testing due to pigsÕ precocial nature (34,35). In addition, previous work has shown that at birth, the percentage of adult brain weight is more similar in piglets (25%) and humans (26%) than in other common animal models used to study brain development [i.e., monkey (76%) and rat (12%) (29)].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite the prevalence of this problem, the mechanisms for the effects of iron deficiency on cognition are poorly understood. The pig may be an excellent preclinical model in which to study the mechanisms underlying iron deficiency-induced cognitive impairment in human neonates due to similar brain growth and structure (27,28,30), limited iron stores at birth (33), and the ease of early life cognitive testing due to pigsÕ precocial nature (34,35). In addition, previous work has shown that at birth, the percentage of adult brain weight is more similar in piglets (25%) and humans (26%) than in other common animal models used to study brain development [i.e., monkey (76%) and rat (12%) (29)].…”
Section: Discussionmentioning
confidence: 99%
“…Piglets were scanned using a Siemens MAGNETOM Trio 3T Imager using a Siemens 32-channel head coil (Siemens). Brain images were acquired using a 3D T1-weighted, magnetization-prepared, rapid gradient-echo sequence, as previously described (30,39), with a final voxel size of 0.35 mm 3 0.35 mm 3 1.0 mm. Volumes were determined using a protocol previously described (30), which included 3D visualization software (AMIRA, Visage Imaging) and a Wacom Cintiq 21UX graphic input screen with a stylus pen (Wacom).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, MRI has been used to assess structural brain development in piglets and human infants [11,12]. For example, Fang et al used T1-weighted images and histological analyses to evaluate myelination in the fiber tracts of the central nervous system (CNS) during development for fifteen female Bamamini piglets aged 2-6 months [13].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, their physical size allows neuroimaging instruments designed for humans to be used with piglets. Indeed, structural MRI, functional MRI, and positron emission tomography have all been conducted in pigs (Conrad et al, 2012b; Fang et al, 2005; Jakobsen et al, 2006). Additionally, piglets can undergo cognitive testing at a young age and show greater overlap with humans in genes involved in immunity compared to rodents (Dawson, 2011; Dilger and Johnson, 2010; Meurens et al, 2012).…”
Section: Introductionmentioning
confidence: 99%